A Palm Grove in Smyrna and the Negotiation of Judean Difference - Smith, Daniel Charles (Journal of ancient Judaism, 2025)
Around 124 CE, a group of unusually-named Judeans promised funds for the construction of a palm grove complex in the Western Anatolian city of Smyrna. An inscription, IvSmyr 697, names "those former residents of Judea" (οἱ ποτὲ Ἰουδαῖοι) alongside several elite individuals from the Roman polis who together donated capital to build a φοινικών (palm grove complex) in the city. This paper focuses on the strategies employed by these elite Judeans in the shadow of the Flavian subjugation of Judea and the diaspora rebellions of the early second century CE. What material and social conditions shape this act of patronage? What strategies are at work among these Judeans in their political moment, and how might their actions have been received in Roman Smyrna? Expanding upon an at times limited spectrum assigning Judeans to positions of assimilation, resistance, or ambivalence toward Roman imperial culture writ large, this paper draws on Religious Studies scholarship on imperialism and religion to analyze IvSmyr 697 to suggest a more diverse and multivalent social history of Judeans in the Roman diaspora.